AB0314 Awareness and Acceptance of Biosimilars by Rheumatologists in Eleven Eu Countries. (15th July 2016) - Kellner, H.; Domènech, E.; Lakatos, P.L.; Marsal, J.; Agboton, C.; Cassese, M.; Georgitseas, N.; Anwar, S.; Venugopal, A.; Audhya, P.
Abstract : Background: The first infliximab biosimilar was approved in Europe in Sept. 2013 for all indications authorised for originator infliximab, including those in rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Confusion exists around differences between biologics and biosimilars, the definition of a biosimilar and the process by which they are manufactured. In addition, there are varying levels of comfort in the types of patients to whom biosimilars could be prescribed. Objectives: We aimed to understand rheumatologists' current perspectives and knowledge on biosimilars, including regulatory aspects and manufacturing principles, as well as comfort with prescribing. Methods: 222 rheumatologists chosen randomly across 11 countries (Finland, France, Germany, Hungary, Ireland, Italy, Norway, Portugal, Spain, Sweden, and UK) participated in a web-based survey from Jun. to Aug. 2015. Key eligibility criteria: being in a practice with at least 30% of patients with Rheumatoid Arthritis or 5% with Ankylosing Spondylitis; at least 15% of these treated with a biologic; physicians in the survey prescribed infliximab (originator or biosimilar) to at least one patient and have access to biosimilar infliximab (able to prescribe biosimilar infliximab). Most (72%) had prescribed biosimilar infliximab to at least one patient. Results: 97% of rheumatologists indicated being familiar or very familiar with biosimilars. Despite a high level of familiarity, only 48% correctly identified the EMA definition of a biosimilar; the remainder incorrectly defined biosimilars as the equivalent of generics for biologics (16%) or as similar biologics having the same mechanism of action as the originator (36%). 65% of rheumatologists cited either limited or no knowledge of biologic manufacturing processes. Most rheumatologists preferred to prescribe biosimilars to naïve patients or those who stopped responding to their current biologic. On a scale of 1 to 10 (10 = extremely comfortable), rheumatologists rated their level of comfort in prescribing biosimilars as 6.5 (significantly lower than gastroenterologists answering an identical question in a parallel survey; mean = 6.9, p=0.002 ). There was a general correlation between the length of exposure to biosimilars and willingness to prescribe, although exceptions were noted (e.g., Portugal, Spain). Knowledge regarding biosimilar manufacturing standards and comfort in prescribing were not correlated. Conclusions: Knowledge and awareness of biosimilars is growing among EU rheumatologists and there are high levels of comfort in prescribing biosimilars; however, confusion still exists with regard to definitions, regulations and manufacturing standards. Disclosure of Interest: H. Kellner: None declared, E. Domènech Grant/research support from: MSD, AbbVie, Hospira, Kern Pharma, Celgene, and Jansenn, Speakers bureau: MSD, AbbVie, Hospira, Kern Pharma, Celgene, and Jansenn, P. Lakatos Grant/research support from: AbbVie, MSD and Hospira, Speakers bureau: AbbVie, Celltrion, EGIS, Falk Pharma GmbH, Ferring, Hospira, Kyowa Hakko Kirin Pharma, Mitsubishi Tanabe Pharma Corporation, MSD, Otsuka, Pharmacosmos, Roche and Takeda, J. Marsal: None declared, C. Agboton: None declared, M. Cassese: None declared, N. Georgitseas: None declared, S. Anwar: None declared, A. Venugopal: None declared, P. Audhya: None declared